CYBERATTACKS ON THE ACCOUNTING PROFESSION :A LITERATUR REVIEW - Surya, Dhimas; Doddy Setiawan; Y. Anni Aryani; Taufiq Arifin (Media Riset Akuntansi, Auditing & Informasi, 2024)
This research reviews the literature on cyberattacks against accounting information systems, focusing on their causes, impacts and mitigation strategies. The results of the systematic mapping show that cyberattacks are caused by various internal and external factors, including system vulnerabilities, human error, and technological evolution. The impact of cyberattacks can be significant, including financial loss, reputational damage, compromise of financial data, erosion of trust, and operational disruption. Addressing these challenges requires a proactive approach that combines technology, policy and education. Investment in cybersecurity, awareness training, and a strong security culture are essential to mitigate cyber risks. Further research is needed to evaluate the effectiveness of cybersecurity strategies, the role of cybersecurity culture, rapid detection and response methods, integration of new technologies, and the impact of regulations. By raising awareness and implementing proactive measures, the accounting profession can improve its cybersecurity posture and protect critical financial information from cyber threats.